Evaluasi Pendidikan : Prosedur, Fungsi dan Manfaat - Adjiji, Fatma; Rizki Mulyono, Edy; Zaki, Muhammad; Nurhadi, Nurhadi (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
This study aims to examine the procedures, functions, and benefits of educational evaluation in order to improve the quality of learning. The method used is a literature review with a descriptive qualitative approach and content analysis techniques applied to various scholarly sources and policy documents. The findings indicate that educational evaluation must be conducted systematically, encompassing planning, implementation, supervision, and result analysis, using valid and reliable instruments. Evaluation serves as a tool for selection, diagnosis, feedback, and accountability, and provides significant benefits in enhancing learning quality, student motivation, curriculum development, and the assessment of teacher and institutional performance. Therefore, evaluation must be understood and implemented objectively and continuously as a strategic effort to support educational transformation and quality improvement.